Emerging Trends in Cinema Education: A Bibliometric Analysis - Faturrahman, Faturrahman; Saputra, Wahyu Nanda Eka (Jurnal Kajian Bimbingan dan Konseling, 2024)
Cinema education has evolved significantly and become an effective medium in various fields, but comprehensive research analyzing its publication trends is still limited. This study uses a bibliometric analysis method with the PRISMA model to identify, select, and filter articles in Scopus-indexed journals from 1948 to 2024 (n= 650), with data analyzed using the VOSViewer application. The keywords used are cinema education, cinematherapy, film therapy, video therapy, cinema therapy, or video therapy. Results show a significant upward trend in publications on cinema education in the last decade, with a peak in the 2021-2023 period. The United States is the country with the largest contribution, followed by the United Kingdom and Israel. Lesley University was the affiliate that produced the most publications, while the University of Haifa had the highest number of citations. The journal "Arts in Psychotherapy" contributed the most publications on cinema education. Shoshi Keisari was identified as the researcher with the most publications, while David Read Johnson and Hod Orkibi had the greatest impact based on the number of citations. The findings also showed that the dominant themes in the publications were drama therapy, psychotherapy, and cinematherapy. This study provides important insights into the development, dynamics, and collaboration of research in cinema education, which can serve as a basis for researchers and practitioners in developing future research strategies and collaborations.